Evaluating alcohol intoxication management services: the EDARA mixed-methods study - Simon C Moore; Davina Allen; Yvette Amos; Joanne Blake; Alan Brennan; Penny Buykx; Steve Goodacre; Laura Gray; Andy Irving; Alicia O'Cathain; Vaseekaran Sivarajasingam; Tracey Young (National Institute for Health Research, 2020)
Background: Front-line health-care services are under increased demand when acute alcohol intoxication is most common, which is in night-time environments. Cities have implemented alcohol intoxication management services to divert the intoxicated away from emergency care. Objectives: To evaluate the effectiveness, cost-effectiveness and acceptability to patients and staff of alcohol intoxication management services and undertake an ethnographic study capturing front-line staff's views on the impact of acute alcohol intoxication on their professional lives. Methods: This was a controlled mixed-methods longitudinal observational study with an ethnographic evaluation in parallel. Six cities with alcohol intoxication management services were compared with six matched control cities to determine effects on key performance indicators (e.g. number of patients in the emergency department and ambulance response times). Surveys captured the impact of alcohol intoxication management services on the quality of care for patients in six alcohol intoxication management services, six emergency departments with local alcohol intoxication management services and six emergency departments without local alcohol intoxication management services. The ethnographic study considered front-line staff perceptions in two cities with alcohol intoxication management services and one city without alcohol intoxication management services. Results: Alcohol intoxication management services typically operated in cities in which the incidence of acute alcohol intoxication was greatest. The per-session average number of attendances across all alcohol intoxication management services was low (mean 7.3, average minimum 2.8, average maximum 11.8) compared with the average number of emergency department attendances per alcohol intoxication management services session (mean 78.8), and the number of patients diverted away from emergency departments, per session, required for services to be considered cost-neutral was 8.7, falling to 3.5 when ambulance costs were included. Alcohol intoxication management services varied, from volunteer-led first aid to more clinically focused nurse practitioner services, with only the latter providing evidence for diversion from emergency departments. Qualitative and ethnographic data indicated that alcohol intoxication management services are acceptable to practitioners and patients and that they address unmet need. There was evidence that alcohol intoxication management services improve ambulance response times and reduce emergency department attendance. Effects are uncertain owing to the variation in service delivery. Limitations: The evaluation focused on health service outcomes, yet evidence arose suggesting that alcohol intoxication management services provide broader societal benefits. There was no nationally agreed standard operating procedure for alcohol intoxication management services, undermining the evaluation. Routine health data outcomes exhibited considerable variance, undermining opportunities to provide an accurate appraisal of the heterogenous collection of alcohol intoxication management services. Conclusions: Alcohol intoxication management services are varied, multipartner endeavours and would benefit from agreed national standards. Alcohol intoxication management services are popular with and benefit front-line staff and serve as a hub facilitating partnership working. They are popular with alcohol intoxication management services patients and capture previously unmet need in night-time environments. However, acute alcohol intoxication in emergency departments remains an issue and opportunities for diversion have not been entirely realised. The nurse-led model was the most expensive service evaluated but was also the most likely to divert patients away from emergency departments, suggesting that greater clinical involvement and alignment with emergency departments is necessary. Alcohol intoxication management services should be regarded as fledgling services that require further work to realise benefit. Future work: Research could be undertaken to determine if a standardised model of alcohol intoxication management services, based on the nurse practitioner model, can be developed and implemented in different settings. Future evaluations should go beyond the health service and consider outcomes more generally, especially for the police. Future work on the management of acute alcohol intoxication in night-time environments could recognise the partnership between health-care, police and ambulance services and third-sector organisations in managing acute alcohol intoxication. Trial registration: Current Controlled Trials ISRCTN63096364. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 8, No. 24. See the NIHR Journals Library website for further project information.